Sistem Informasi Geografis Pariwisata Kota Semarang - Ambrina Kundyanirum; Kodrat Iman Satoto; Oky Dwi Nurhayati (Jurnal Teknologi dan Sistem Komputer, 2013)
Semarang City is a city that has a uniqueness that is rarely found in other cities, because there is a lowland called the Semarang Bawah and a Highland called Semarang Atas. Many attractions can be visited, such as religious tourism, nature tourism, and culinary tourism.  But this time the local government does not have that information systems can support the information needs fulfillment through khususya internet-based map of the tourism potential possessed.Final project using the Google Map API for creation of Geographic Information Systems, Google Maps is a map that can be viewed using a browser, to be able to display Google Maps on a web needed PHP, JavaScript and a stable internet connection.The results of this application design is the realization of a geographic information system application Semarang City Tourism that can be used to identify and obtain information about the location and how to reach there.